Complete response to exemestane in a patient with a desmoid tumor. (April 2012) - Debled, Marc; Le Loarer, François; Callonnec, Françoise; Soubeyran, Isabelle; Cambon-Michot, Chantal; Dujardin, Franck; Italiano, Antoine
Desmoid tumors are rare mesenchymal neoplasms without metastatic potential. Despite the benign nature of this condition, some patients develop disease progression despite all locoregional options for care. Aggressive forms of desmoid tumors may induce morbidity that can lead to physical impairment and mortality that is occasionally observed as a result of local infiltrative growth and tissue invasion, in particular with abdominal disease. Few therapeutic options are available for patients with recurrent/unresectable desmoid tumors. Several studies have suggested the potential benefit of antiestrogens such as tamoxifen in this setting. Here we report the first description of the efficacy of an aromatase inhibitor in a patient with a desmoid tumor.